Respiratory rates in black and white goats of different ages - Arruda, Francisco de A.V.; Pant, Kant P. (Pesquisa Agropecuaria Brasileira, 2014)
This study was undertaken to measure the frequency of respiration per minute (FR) in weaning and in mature white and black goats during the hot dry season. Maximum variation occurred between 7 a.m. (FR 18.2) and 2 p.m. (FR 33.4). There was no change in the mean FR from around weaning (112 days) to adulthood (2 to 2.5. years), but black goats respired at higher rate than white. The increase in the afternoon FR was significantly in black goats than in white ones.